Drying Cabinet Using UV Lamp - Apriliana, Era; Fithri, Normaliaty (SITEKIN: Jurnal Sains, Teknologi dan Industri, 2023)
Drying clothes is an activity carried out by the community. Uncertain weather, such as rain, causes the movement of drying clothes to be hampered. The uncertain weather factor caused by global warming causes the temperature to change, sometimes, it is hot, and sometimes it rains. This causes clothes not to dry entirely and causes damp garments frequently. In this scientific work, the researcher will make a device that functions as a drying cabinet which is equipped with a temperature sensor and drying time uses a DHT22 sensor temperature sensor and LCD, which works to display the drying process. and the time needed to dry the clothes equipped with a heater which functions as a heat source so that the clothes will dry to the maximum. Measurements were made at several test points in the circuit designed to get the most significant error percentage of 5.5% with an average error of 2 .40 %. The results of the design are carried out by the criteria used. From the results of the tests, the drying process using the tools designed has succeeded in drying clothes to the maximum and minimizing germs.